Pengaruh Debt Financing Dan Equity Financing Terhadap Profit Expense Ratio Pada Bank Syariah Mandiri Tahun 2010-2019 - Deky Anwar; Riski Ananda Amelia (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2020)
Purpose- This study aims to determine the effect of the level of financing with the principle of debt financing and equity financing to profit expense ratio in Bank Syariah Mandiri in 2010-2019. Methods- The sample selection technique uses purposive sampling. In this study, the authors used the method of multiple linear regression analysis. The data analysis technique used is the classic assumption test and multiple linear analysis. Findings- Based on the results of the analysis shows that financing with the principle of debt financing does not affect the profit expense ratio, while financing with the principle of equity financing affects the profit expense ratio.